The use of Youtube in lectures- More copyright shades of grey - Sadler, Pauline; Bunn, Anna (Loganholme, Queensland: Australia and New Zealand Education Law Association, 2011)
The use of technology is nowadays seen as a fundamental component of engaging and innovative teaching in Australian universities. A valuable source of audio-visual material for use in lectures is the YouTube website, but where lectures are recorded by the university and made available on an online learning platform there is potential for breach of copyright to occur. This article examines the provisions of the Copyright Act 1968 (Cth) to assess the extent to which the university, and the individual lecturer, may be liable for breach of copyright. The YouTube terms of service are also examined to determine what action YouTube might take against the university.